Pengembangan Bahan Ajar Berbasis Instructional Approach Learning pada Mata Kuliah Kemampuan Dasar Mengajar Kimia - Kurniati, Tuti (Jurnal Inovasi Pendidikan Kimia, 2022)
Teachers must have competency standards in carrying out their duties. The competencies that must be possessed by professional teachers are pedagogic competence, professional competence, personal competence and social competence. In order for students to master the four competence and basic skills of teaching it is necessary to develop modul materials based on instructional approach learning. The purpose of this research is to develop modul materials. Ths research following 3D model of Thiagarajan which consists of the definition stage, the design stage and the development stage. Â The result of the research shows are the validity of the material aspect is 97.5% and the media is 87.5% in valid criteria. Practicality based on the value of the student response questionnaire in the individual trial was 95.8% and the small group test wa 89.6% which was considered very practical.